solve the linear equation 4 (x-2) - 3 (2x-3) = 2(x-1)
Answers
Answered by
8
Step-by-step explanation:
x=3/4
plz mark it as brainliest
Attachments:
![](https://hi-static.z-dn.net/files/d46/9a84323429b266070b866b4450720db6.jpg)
Answered by
7
Answer:
3/4
Step-by-step explanation:
4(x-2)-3(2x-3)=2(x-1)
4x-8-6x+9=2x-2
-2x+1=2x-2
-2x-2x=-2-1
-4x=-3
x=-3/-4
×=3/4
MARK AS BRAINLIEST
Similar questions
Math,
6 months ago
India Languages,
6 months ago
Accountancy,
6 months ago
Hindi,
1 year ago
Math,
1 year ago
Math,
1 year ago